An Approach to Estimate SCC Growing Rate in Slow Strain Rate Tensile Test Based on EPFEM - Shuai Wang; He Xue; Yinghao Cui; Fuqiang Yang; Rui Guo (Advances in Materials Science and Engineering)
The slow strain rate tensile test (SSRT) is a common means to investigate stress corrosion cracking (SCC) in key engineering structural materials of light-water reactors, and it is an important task to real-time monitor the crack growing length and rate of the specimen during the test. Because the specimen is placed in an autoclave with high-pressure and high-temperature water environment-simulated light-water reactor, the current potential drop method, which includes current potential drop (DCPD) and alternating current potential drop (ACPD), is the main means to real-time monitor crack growth rate in the SCC test. As a supplementary means to obtain the crack growth rate during the test, the SSRT process of nickel-based Alloy 600 CT specimens is investigated by using the elastic-plastic finite element method (EPFEM) in this paper. Based on the consideration that both the elastic-plastic deformation and crack length of the specimen would affect the relationship between the load and the displacement of the loading point during the SSRT test, the relationship between the loading point displacement caused by crack propagation ΔLc and plastic deformation ΔLp is separated by EPFEM. Then, the SCC crack growth rate and the real-time crack length are obtained. This proposed approach could be used to improve the test results in the SSRT test.